Widespread Shrubification on European Mountain Summits - Thomas Vanneste; Harald Pauli; Stefan Dullinger; Bente J. Graae; Otar Abdaladze; José Luis Benito Alonso; Christopher Andrews; Peter Barančok; Manfred Bardy‐Durchhalter; Haben Blondeel; Pau Carnicero; Emmanuel Corcket; et al. (Global Change Biology, 2026)
Shrubs are expanding across the cold ecosystems of our planet with potentially profound consequences for their biodiversity and functioning. However, evidence is still strongly biased towards the Arctic tundra, while a large‐scale assessment of shrub expansion in alpine areas above the elevational treeline is missing so far. Here we quantified shrub cover changes over the past two decades in 576 permanent plots of 1 m 2 spread across the alpine vegetation belt of Europe's major mountain chains. Total shrub cover clearly increased in the plots with an average rate of about 2.6% per m 2 per decade (95% CI = 1.9%–3.4%), and this expansion was more pronounced for evergreen (2.0% per m 2 per decade, CI = 1.3%–2.7%) than for deciduous species (1.7% per m 2 per decade, CI = 0.9%–2.4%). The magnitude of individual species' cover shifts was positively associated with their plant height, but negatively with their leaf nitrogen content and light affinity. In sum, we show that shrub expansion is a widespread phenomenon also in the alpine zone of European mountains, with potentially far‐reaching consequences for alpine plant dynamics, soil microclimates, snow patterns, carbon cycling, food chains and livelihoods.

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Inter-laboratory validation of an ISO test method for measuring enzyme activities in soil samples using colorimetric substrates - Nathalie Cheviron; Virginie Grondin; Christelle Marrauld; Françoise Poiroux; Isabelle Bertrand; Josiane Abadie; Pascal Pandard; Wassila Riah-Anglet; Caroline Dubois; Stanislav Malý; Catarina R. Marques; Inmaculada Valverde Asenjo; et al. (Environmental Science and Pollution Research, 2022)

Directional turnover towards larger‐ranged plants over time and across habitats - Ingmar R. Staude; Henrique M. Pereira; Gergana N. Daskalova; Markus Bernhardt‐Römermann; Martin Diekmann; Harald Pauli; Hans Van Calster; Mark Vellend; Anne D. Bjorkman; Jörg Brunet; Pieter De Frenne; Radim Hédl; et al. (Ecology Letters, 2022)
Species turnover is ubiquitous. However, it remains unknown whether certain types of species are consistently gained or lost across different habitats. Here, we analysed the trajectories of 1827 plant species over time intervals of up to 78 years at 141 sites across mountain summits, forests, and lowland grasslands in Europe. We found, albeit with relatively small effect sizes, displacements of smaller‐ by larger‐ranged species across habitats. Communities shifted in parallel towards more nutrient‐demanding species, with species from nutrient‐rich habitats having larger ranges. Because these species are typically strong competitors, declines of smaller‐ranged species could reflect not only abiotic drivers of global change, but also biotic pressure from increased competition. The ubiquitous component of turnover based on species range size we found here may partially reconcile findings of no net loss in local diversity with global species loss, and link community‐scale turnover to macroecological processes such as biotic homogenisation.

A common soil temperature threshold for the upper limit of alpine grasslands in European mountains - Sarah Bürli; Jean-Paul Theurillat; Manuela Winkler; Andrea Lamprecht; Harald Pauli; Christian Rixen; Klaus Steinbauer; Sonja Wipf; Otar Abdaladze; Christopher Andrews; Peter Barančok; José Luis Benito-Alonso; et al. (Alpine Botany, 2021)
While climatic research about treeline has a long history, the climatic conditions corresponding to the upper limit of closed alpine grasslands remain poorly understood. Here, we propose a climatic definition for this limit, the ‘grassline’, in analogy to the treeline, which is based on the growing season length and the soil temperature. Eighty-seven mountain summits across ten European mountain ranges, covering three biomes (boreal, temperate, Mediterranean), were inventoried as part of the GLORIA project. Vascular plant cover was estimated visually in 326 plots of 1 × 1 m. Soil temperatures were measured in situ for 2–7 years, from which the length of the growing season and mean temperature were derived. The climatic conditions corresponding to 40% plant cover were defined as the thresholds for alpine grassland. Closed vegetation was present in locations with a mean growing season soil temperature warmer than 4.9 °C, or a minimal growing season length of 85 days, with the growing season defined as encompassing days with daily mean ≥ 1 °C. Hence, the upper limit of closed grasslands was associated with a mean soil temperature close to that previously observed at the treeline, and in accordance with physiological thresholds to growth in vascular plants. In contrast to trees, whose canopy temperature is coupled with air temperature, small-stature alpine plants benefit from the soil warmed by solar radiation and consequently, they can grow at higher elevations. Since substrate stability is necessary for grasslands to occur at their climatic limit, the grassline rarely appears as a distinct linear feature.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Evaluating the potential of full‐waveform lidar for mapping pan‐tropical tree species richness - Suzanne M. Marselis; Katharine Abernethy; Alfonso Alonso; John Armston; Timothy R. Baker; Jean‐Francois Bastin; Jan Bogaert; Doreen S. Boyd; Pascal Boeckx; David F. R. P. Burslem; Robin Chazdon; David B. Clark; et al. (Global Ecology and Biogeography, 2020)
Aim Mapping tree species richness across the tropics is of great interest for effective conservation and biodiversity management. In this study, we evaluated the potential of full‐waveform lidar data for mapping tree species richness across the tropics by relating measurements of vertical canopy structure, as a proxy for the occupation of vertical niche space, to tree species richness. Location Tropics. Time period Present. Major taxa studied Trees. Methods First, we evaluated the characteristics of vertical canopy structure across 15 study sites using (simulated) large‐footprint full‐waveform lidar data (22 m diameter) and related these findings to in‐situ tree species information. Then, we developed structure–richness models at the local (within 25–50 ha plots), regional (biogeographical regions) and pan‐tropical scale at three spatial resolutions (1.0, 0.25 and 0.0625 ha) using Poisson regression. Results The results showed a weak structure–richness relationship at the local scale. At the regional scale (within a biogeographical region) a stronger relationship between canopy structure and tree species richness across different tropical forest types was found, for example across Central Africa and in South America [ R 2 ranging from .44–.56, root mean squared difference as a percentage of the mean (RMSD%) ranging between 23–61%]. Modelling the relationship pan‐tropically, across four continents, 39% of the variation in tree species richness could be explained with canopy structure alone ( R 2 = .39 and RMSD% = 43%, 0.25‐ha resolution). Main conclusions Our results may serve as a basis for the future development of a set of structure–richness models to map high resolution tree species richness using vertical canopy structure information from the Global Ecosystem Dynamics Investigation (GEDI). The value of this effort would be enhanced by access to a larger set of field reference data for all tropical regions. Future research could also support the use of GEDI data in frameworks using environmental and spectral information for modelling tree species richness across the tropics.

Heterogeneity of the rice microbial community of the Chinese centuries‐old Honghe Hani rice terraces system - Pascal Alonso; Laurence Blondin; Pierre Gladieux; Frédéric Mahé; Hervé Sanguin; Romain Ferdinand; Denis Filloux; Eric Desmarais; Frédérique Cerqueira; Baihui Jin; Huichuan Huang; Xiahong He; et al. (Environmental Microbiology, 2020)
Summary The Honghe Hani rice terraces system (HHRTS) is a traditional rice cultivation system where Hani people cultivate remarkably diverse rice varieties. Recent introductions of modern rice varieties to the HHRTS have significantly increased the severity of rice diseases within the terraces. Here, we determine the impacts of these recent introductions on the composition of the rice‐associated microbial communities. We confirm that the HHRTS contains a range of both traditional HHRTS landraces and introduced modern rice varieties and find differences between the microbial communities of these two groups. However, this introduction of modern rice varieties has not strongly impacted the overall diversity of the HHRTS rice microbial community. Furthermore, we find that the rice varieties (i.e. groups of closely related genotypes) have significantly structured the rice microbial community composition (accounting for 15%–22% of the variance) and that the core microbial community of HHRTS rice plants represents less than 3.3% of all the microbial taxa identified. Collectively, our study suggests a highly diverse HHRTS rice holobiont (host with its associated microbes) where the diversity of rice hosts mirrors the diversity of their microbial communities. Further studies will be needed to better determine how such changes might impact the sustainability of the HHRTS.

Climate‐induced changes in the suitable habitat of cold‐water corals and commercially important deep‐sea fishes in the North Atlantic - Telmo Morato; José‐Manuel González‐Irusta; Carlos Dominguez‐Carrió; Chih‐Lin Wei; Andrew Davies; Andrew K. Sweetman; Gerald H. Taranto; Lindsay Beazley; Ana García‐Alegre; Anthony Grehan; Pascal Laffargue; Francisco Javier Murillo; et al. (Global Change Biology, 2020)
The deep sea plays a critical role in global climate regulation through uptake and storage of heat and carbon dioxide. However, this regulating service causes warming, acidification and deoxygenation of deep waters, leading to decreased food availability at the seafloor. These changes and their projections are likely to affect productivity, biodiversity and distributions of deep‐sea fauna, thereby compromising key ecosystem services. Understanding how climate change can lead to shifts in deep‐sea species distributions is critically important in developing management measures. We used environmental niche modelling along with the best available species occurrence data and environmental parameters to model habitat suitability for key cold‐water coral and commercially important deep‐sea fish species under present‐day (1951–2000) environmental conditions and to project changes under severe, high emissions future (2081–2100) climate projections (RCP8.5 scenario) for the North Atlantic Ocean. Our models projected a decrease of 28%–100% in suitable habitat for cold‐water corals and a shift in suitable habitat for deep‐sea fishes of 2.0°–9.9° towards higher latitudes. The largest reductions in suitable habitat were projected for the scleractinian coral Lophelia pertusa and the octocoral Paragorgia arborea , with declines of at least 79% and 99% respectively. We projected the expansion of suitable habitat by 2100 only for the fishes Helicolenus dactylopterus and Sebastes mentella (20%–30%), mostly through northern latitudinal range expansion. Our results projected limited climate refugia locations in the North Atlantic by 2100 for scleractinian corals (30%–42% of present‐day suitable habitat), even smaller refugia locations for the octocorals Acanella arbuscula and Acanthogorgia armata (6%–14%), and almost no refugia for P. arborea . Our results emphasize the need to understand how anticipated climate change will affect the distribution of deep‐sea species including commercially important fishes and foundation species, and highlight the importance of identifying and preserving climate refugia for a range of area‐based planning and management tools.

Spectrally decomposed dark-to-light transitions in Synechocystis sp. PCC 6803 - Alonso M. Acuña; Pascal van Alphen; Filipe Branco dos Santos; Rienk van Grondelle; Klaas J. Hellingwerf; Ivo H. M. van Stokkum (Photosynthesis Research, 2018)

A method to decompose spectral changes in Synechocystis PCC 6803 during light-induced state transitions - Alonso M. Acuña; Radek Kaňa; Michal Gwizdala; Joris J. Snellenburg; Pascal van Alphen; Bart van Oort; Diana Kirilovsky; Rienk van Grondelle; Ivo H. M. van Stokkum (Photosynthesis Research, 2016)

The rich sides of mountain summits – a pan‐European view on aspect preferences of alpine plants - Manuela Winkler; Andrea Lamprecht; Klaus Steinbauer; Karl Hülber; Jean‐Paul Theurillat; Frank Breiner; Philippe Choler; Siegrun Ertl; Alba Gutiérrez Girón; Graziano Rossi; Pascal Vittoz; Maia Akhalkatsi; et al. (Journal of Biogeography, 2016)
Aim In the alpine life zone, plant diversity is strongly determined by local topography and microclimate. We assessed the extent to which aspect and its relatedness to temperature affect plant species diversity, and the colonization and disappearance of species on alpine summits on a pan‐European scale. Location Mountain summits in Europe's alpine life zone. Methods Vascular plant species and their percentage cover were recorded in permanent plots in each cardinal direction on 123 summits in 32 regions across Europe. For a subset from 17 regions, resurvey data and 6‐year soil temperature series were available. Differences in temperature sum and Shannon index as well as species richness, colonization and disappearance of species among cardinal directions were analysed using linear mixed‐effects and generalised mixed‐effects models, respectively. Results Temperature sums were higher in east‐ and south‐facing aspects than in the north‐facing ones, while the west‐facing ones were intermediate; differences were smallest in northern Europe. The patterns of temperature sums among aspects were consistent among years. In temperate regions, thermal differences were reflected by plant diversity, whereas this relationship was weaker or absent on Mediterranean and boreal mountains. Colonization of species was positively related to temperature on Mediterranean and temperate mountains, whereas disappearance of species was not related to temperature. Main conclusions Thermal differences caused by solar radiation determine plant species diversity on temperate mountains. Advantages for plants on eastern slopes may result from the combined effects of a longer diurnal period of radiation due to convection cloud effects in the afternoon and the sheltered position against the prevailing westerly winds. In northern Europe, long summer days and low sun angles can even out differences among aspects. On Mediterranean summits, summer drought may limit species numbers on the warmer slopes. Warmer aspects support a higher number of colonization events. Hence, aspect can be a principal determinant of the pace of climate‐induced migration processes.